The Theological Discourse on Divine Attributes: A Comparative Study of Ashʿarite, Māturīdite, and Muʿtazilite Perspectives - Zarkasyi, Amal Fathullah; Syamil, Ahmad Hisyam; Kusuma, Amir Reza; Wijaya, Agarin Muqsit (Center of Islamic and Occidental Studies, 2025)
This study examines the theological perspectives on Divine Attributes among the Ashʿarī, Māturīdī, and Muʿtazilite schools, highlighting their doctrinal differences and methodological approaches. While the Ashʿarīs affirm Divine Attributes as neither identical to nor separate from God’s essence, the Māturīdīs emphasize rational-textual balance, rejecting anthropomorphism without negating attributes. In contrast, the Muʿtazilites deny eternal attributes, arguing they compromise God’s unity (tawḥīd), and interpret scriptural anthropomorphisms metaphorically. Employing a critical-analytical method, this research reveals how these schools navigate the tension between divine transcendence and scriptural literalism. The findings underscore the Ashʿarī-Māturīdī alignment against Muʿtazilite rationalism, while noting subtle divergences between them. The study contributes to broader Islamic theological discourse by clarifying these schools’ positions on Divine Attributes.